Reinfected Revised TKA Resolves With an Aggressive Protocol and Antibiotic Infusion - Whiteside, Leo A. (Springer-Verlag, 2011)
BACKGROUND: Revision of failed two-stage revision TKA for infection is challenging, and amputation often is the only alternative. QUESTIONS/PURPOSES: We asked whether reinfection after two-stage revision for infection could be controlled with an aggressive revision protocol and intraarticular antibiotic infusion. METHODS: We retrospectively reviewed 18 patients (12 women, six men) who underwent revision for failed reimplantation between January 1999 and January 2008. Mean time from revision for infection to rerevision for reinfection was 5 months (range, 1–18 months). All knees were treated with an individualized protocol that included aggressive exposure, extensive débridement, uncemented components, closure with muscle flaps (seven knees) and other plastic surgery procedures (three knees), and direct antibiotic infusion through Hickman catheters for 6 weeks. Ten knees had one-stage revision; five had débridement, cement spacer, and revision surgery 3 to 4 months later; and three had extensive soft tissue reconstruction before revision surgery. The minimum followup was 2.3 years (mean, 6.1 years; range, 2.3–12.0 years). RESULTS: The mean Knee Society scores improved from 33 preoperatively to 76. Seventeen of the 18 had control of infection and achieved durable fixation and a closed wound. One patient had recurrent infection 13 months after one-stage revision, was revised, and remained asymptomatic 28 months postoperatively after redébridement and vancomycin infusion for 6 weeks. In one patient, soft tissue closure was not obtained and the patient required amputation. CONCLUSIONS: Extensile exposure, débridement, and soft tissue flaps for closure combined with uncemented fixation of revision implants and antibiotic infusion into the knee controlled reinfection after revision TKA. LEVEL OF EVIDENCE: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.